Handbook of Management Consulting - Greiner, Larry E. (Thomson South-Western, 2005)
This book provides a thorough examination of a variety of specialties within the broad range of management consulting. A book of such scope and depth could only be written by a large number of experts. Each chapter is written by a leading expert in one of the many specialties related to management consulting. Together, all 27 contributors take the reader through an industry that is currently undergoing significant change. While covering all the major practice areas of consulting, the book also offers new insights into change processes and addresses compelling management issues now facing consulting firms. Every practicing consultant and firm needs this bookÂ's broad perspective and its treatment of specific areas of content in order to prepare them for a successful future in a highly competitive business environment. Presently, there is no book on the market that takes such an advanced look at both the complexity and multiple aspects of consulting. Ideas presented by the many consulting experts are thoughtful and provocative. Their sage advice on future developments in the field is not to be missed.